International Financial Institutions and Health in Egypt and Tunisia: Change or Continuity?. (January 2013) - Ismail, Sharif
The revolutions in Egypt and Tunisia appeared to herald a re-casting of International Monetary Fund and World Bank policy across the region. Public pronouncements by the heads of both institutions in the months following February 2011 acknowledged flaws in their approach to macroeconomic advice, against a background of worsening socioeconomic indicators, widespread youth unemployment, and widening health inequalities. Evidence on the ground, however, suggests continuity rather than change in international financial institution policies in Egypt and Tunisia, notwithstanding the emergence of a powerful new player—the European Bank for Reconstruction and Development. In the long term, new electoral realities and hardening public opposition in both countries seem likely to force a fundamentally different relationship between regional governments and the major international financial institutions than existed before 2011.